No survival benefit associated with routine surveillance imaging for Hodgkin lymphoma in first remission: a Danish‐Swedish population‐based observational study. (5th February 2016) - Jakobsen, Lasse H.; Hutchings, Martin; de Nully Brown, Peter; Linderoth, Johan; Mylam, Karen J.; Molin, Daniel; Johnsen, Hans E.; Bøgsted, Martin; Jerkeman, Mats; El‐Galaly, Tarec C.
Summary: The use of routine imaging for patients with classical Hodgkin lymphoma (HL) in complete remission (CR) is controversial. In a population‐based study, we examined the post‐remission survival of Danish and Swedish HL patients for whom follow‐up practices were different. Follow‐up in Denmark included routine imaging, usually for a minimum of 2 years, whereas clinical follow‐up without routine imaging was standard in Sweden. A total of 317 Danish and 454 Swedish comparable HL patients aged 18–65 years, diagnosed in the period 2007–2012 and having achieved CR following ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine)/BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisone) therapy, were included in the study. The cumulative progression rates in the first 2 years were 4% (95% confidence interval [CI] 1–7) for patients with stage I–II disease vs. 12% (95% CI 6–18) for patients with stage III–IV disease. An imaging‐based follow‐up practice was not associated with a better post‐remission survival in general ( P  = 0·2) or in stage‐specific subgroups ( P  = 0·5 for I–II and P  = 0·4 for III–IV). Age ≥45 years was the only independent adverse prognostic factor for survival. In conclusion, relapse of HL patients with CR is infrequent and systematic use of routine imaging in these patients does not improve post‐remission survival. The present study supports clinical follow‐up without routine imaging, as encouraged by the recent Lugano classification.